If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11.74 = -1log(x) Multiply glo * x 11.74 = -1glox Solving 11.74 = -1glox Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add 'glox' to each side of the equation. 11.74 + glox = -1glox + glox Combine like terms: -1glox + glox = 0 11.74 + glox = 0 Add '-11.74' to each side of the equation. 11.74 + -11.74 + glox = 0 + -11.74 Combine like terms: 11.74 + -11.74 = 0.00 0.00 + glox = 0 + -11.74 glox = 0 + -11.74 Combine like terms: 0 + -11.74 = -11.74 glox = -11.74 Divide each side by 'lox'. g = -11.74l-1o-1x-1 Simplifying g = -11.74l-1o-1x-1
| 4x-8-2x+3=-10x+7+12x+5 | | 42s+s=8322 | | 4(4x-9)+9x= | | 9x+6(80)=7x+560 | | 6y=-2x | | 8x+9=9x+7 | | 6+3x+4x^2+2x^3=0 | | (6-8i)(6+8i)= | | 3(t-5)-t=7 | | 2x+2y=2809.30 | | 2(5x-6)=4[x-3x+30] | | 100x^2-21=110 | | 4(3x-9)-5=4(x-5)+27 | | 4y^3+27y^2+27=0 | | 27y^2+27=0 | | 3-4*6+3= | | 4(3x-8)-5=4(x-5)+15 | | (11x+26)-3= | | Y^6+9y^4-4y^3+27y^2+27=0 | | -7(2c+5)=(c-6) | | 8y-9=12y+15 | | 5x-(2x+4)=14 | | x^2-5x-2.25=0 | | Y=(3x+8)(x-9) | | 6+(3x-4)-(7x+11)= | | 8(7x-6)=27 | | x+20=5x+8 | | x*0.022=1 | | 12y-13=7y+12 | | 4-23=8x-6-7x | | 2(3x)+5x=770 | | 2x+11=21-3x |